Providing of core stability exercise increase the core muscle strength of adult male Balinese vocational polytechnic volleyball athletes - Alifia Dwi Lestari; Ari Wibawa; Anak Ayu Nyoman Trisna Narta Dewi; I Wayan Sugiritama (Bali Anatomy Journal, 2020)
Background: Central Management of Indonesian Volleyball Association admits that volleyball achievements have not been maximized, so they need to be improved. The core muscle have a role in each volleyball technique so that very important to increase core muscle strength which also impacts on the extremities, furthermore, the strength play a role to another biomotor and impact athlete’s performance and achievement. Aim: to prove that providing of core stability exercise increase the core muscle strength of male volleyball athletes aged 18-25 years old in the volleyball unit of student activities at Bali Vocational Polytechnic. Method: an experimental study using a one group pre-test and post-test design with 22 total samples. Core muscle strength measured using one minute sit up test. Results: Hypothesis test using paired sample T-test with p value= 0,000 (p <0.005) statistically showed a significant increase in core muscle strength. Conclusion: based on statistical tests, providing core stability exercise increase the core muscles strength of male volleyball athletes in the volleyball unit of student activities at Bali Vocational Polytechnic.